Determining elements of design thinking implementation in schools using fuzzy delphi method / Adila Md Hashim, Sharipah Ruzaina Syed Aris and Chan Yuen Fook - Md Hashim, Adila; Syed Aris, Sharipah Ruzaina; Fook, Chan Yuen (Universiti Teknologi MARA, 2022)
Design thinking is a design-based learning strategy that flourishes on experiential learning and evolves from the study of unique ways to solve real-world problems. The growing interest in embedded design thinking in educational contexts has given the opportunity for design thinking to be utilised by younger students in schools. This study aims to identify the elements of design thinking implementation for teachers to plan a design-based learning strategy in schools. A total of eight experts were selected to analyse the fuzziness consensus of experts. All collected data were analysed using the Fuzzy Delphi Method. The results show that 40 of the 54 elements meet the conditions in which the threshold value, d is less than 0.2 and the percentage of the expert group is more than 75%. Two elements that were first rejected are added to the list to fulfil the purpose of the design thinking approach. Therefore, based on the consensus of the experts, the elements of design thinking implementation can be used by teachers as a guideline to apply design thinking in schools.